2024
DOI: 10.1002/jgm.3671
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell‐based signature: Prognostic analysis in head and neck squamous cell carcinoma

Zizhao Guo,
Yuxia Zhao,
Meng Xu
et al.

Abstract: BackgroundHead and neck squamous cell carcinoma (HNSC) is a challenging cancer with significant clinical implications. Natural killer (NK) cells have emerged as important players in tumor immunosurveillance, yet their role and potential as prognostic biomarkers in HNSC remain unclear.MethodsQuantitative analysis using multiple algorithms identified FCRL1, KIR3DL2 and ZNF541 as molecules significantly associated with local NK cell infiltration and patient survival. A prognostic model based on these molecules de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…In their study, Zhang et al found an immunologically active subpopulation of HNSCC patients that exhibited higher levels of CD8 + T cell and NK cell activity 27 . There are studies confirming that the expression of NK cell markers is significantly increased in HNSCC samples compared to healthy controls 28 , 29 . Furthermore, Choi et al focused on the progressive progression of HNSCC from normal tissue to precancerous white spots, primary HNSCC, and metastatic tumors.…”
Section: Discussionmentioning
confidence: 96%
“…In their study, Zhang et al found an immunologically active subpopulation of HNSCC patients that exhibited higher levels of CD8 + T cell and NK cell activity 27 . There are studies confirming that the expression of NK cell markers is significantly increased in HNSCC samples compared to healthy controls 28 , 29 . Furthermore, Choi et al focused on the progressive progression of HNSCC from normal tissue to precancerous white spots, primary HNSCC, and metastatic tumors.…”
Section: Discussionmentioning
confidence: 96%